Atomic force microscopy for biomechanical and structural analysis of human dermis: A complementary tool for medical diagnosis and therapy monitoring. Issue 2 (9th January 2018) - Peñuela, Leonardo; Negro, Carola; Massa, Michela; Repaci, Erica; Cozzani, Emanuele; Parodi, Aurora; Scaglione, Silvia; Quarto, Rodolfo; Raiteri, Roberto
Abstract: Skin mechanical properties are usually measured considering the entire skin thickness and very little is known about the mechanical behaviour of individual skin layers. We propose atomic force microscopy (AFM) as a tool to quantify nanoscale changes in the biomechanical properties and ultrastructure of human papillary dermis exposed to different mechanical and physical stimuli. Samples from 3 human skin biopsies were studied: one stretched by obesity, one subjected to a high level of sun exposure and normal skin as control. Slices of the papillary dermis layer were harvested at controlled depths from each skin biopsy and 25 μm 2 areas of each slice were imaged and D‐periodicity of collagen fibres measured by AFM, together with their stiffness. Standard histological analysis was also carried out to correlate biochemical properties and their distribution with stiffness and topography. We obtained similar stiffness values between the sample affected by obesity and the control sample at any depth level into the dermis, while the sun‐exposed sample presented a significantly lower stiffness. Additionally, all samples presented an increase in the stiffness at higher depths into the papillary dermis layer. Collagen fibres close to the epidermis of sample affected either by obesity and sun exposure—the former even more than the latter—are thicker and present a larger D‐period than those in the control sample. Our results open the possibility to use structural and mechanical analysis based on AFM as a complementary tool for medical diagnosis and therapy monitoring.